503. Risk and Timing of Clostridium difficile Infection Relapse After Antibiotic Exposure. (26th November 2018) - Szela, Joel; Venkatappa, Neethi; Sims, Matthew
Abstract: Background: Clostridium difficile infection (CDI) is the most common nosocomial infection, representing 12% of all hospital acquired infections. The risk for CDI is clearly linked to antibiotic (abx) exposure. Several studies, including one from our institution, indicate prophylaxis of patients who recently had CDI with oral vancomycin decreases the risk of a relapse when exposed to abx. In an effort to further analyze this, we examined all patients with CDI in our institution who received any abxafter the CDI and determined how that modified their risk of relapse. Methods: All patients with a positive PCR for C. difficile at our institution between 2012 and 2014 were examined for receipt of abx within 3 months of a positive PCR. Patients who received metronidazole were excluded to remove the potential confounding effect. The relapse rate for all patients, patients who received abx, and patients who did not receive abx were calculated. Timing of the relapse from the last episode of CDI and from receipt of abx were determined. Results: A total of 6, 436 patients were identified, representing 8, 000 episodes of CDI. The relapse rates and timing based on prior CDI episodes and receipt of additional abx prior to relapse are shown in Table 1. There were 1, 375 episodes of CDI where abx were given within 3 months of the episode. Of these patients, 33 received prophylaxis with oral vancomycin, and none of those relapsed within 3 months. Conclusion: While abx clearly are the major risk factor for CDI, the receipt of abx after an episode of CDI does not change the overall rate of CDI relapse. However, when the timing of the relapses after abx is examined, the relapses occur both later in those who received abx than relapses in patients who do not receive abx and shortly after abx. It is likely that abx trigger relapses in patients who otherwise would not have relapsed. Oral vancomycin prophylaxis appears to be effective in preventing relapses in patients given abx after CDI. Disclosures: All authors: No reported disclosures.